Federal Military Government's views on the report of the Industrial Enterprises Panel - Federal Republic of Nigeria (Lagos : Federal Ministry of Information, Printing Division, 1976)
The panel was appointed to examine the Nigerian enterprises promotion decree with a view to report on its implementation, spread of ownership, amendments etc
nmn, 11/04/19
Ref.
Keywords: Africanization; Working class; Industrial entrprises panel